Розробка компонентів системи з оренди автомобілів - Бахмет, І. В. (ХНУРЕ, 2025)
This work is devoted to the development of components for a car rental system. The system enables users to rent an automobile for a specified period wІТh the option of online payment. Users can filter and sort available cars by various parameters, view detailed information about each car, and conveniently manage their personal profile. In addІТion, the system streamlines the overall rental process by providing real-time availabilІТy updates, booking management, and payment tracking. ІТ also maintains a record of each user’s past rentals and transactions, allowing customers to review their history and improve future bookings.
Keywords: оренда автомобілів; автомобільний сервіс